Ethylene/Styrene Copolymerization by (Me3SiC5H4)TiCl2(O-2,6-iPr2-4-RC6H2) (R = H, SiEt3)-MAO Catalysts: Effect of SiMe3 Group on Cp for Efficient Styrene Incorporation - Tiantian Huang; Taiga Fujioka; Daisuke Shimoyama; Kotohiro Nomura (Molecules)
The synthesis and structural analysis of (Me3SiC5H4)TiCl2(OAr) [OAr = O-2,6-iPr2-4-RC6H2; R = H, SiEt3] revealed that it exhibits higher catalytic activities than (tBuC5H4)TiCl2(OAr), Cp*TiCl2(OAr), with efficient comonomer incorporation in ethylene/styrene copolymerization in the presence of a methylaluminoxane (MAO) cocatalyst. The catalytic activity in the copolymerization increased upon increasing the charged styrene concentration along with the increase in the styrene content in the copolymers, whereas the activities of other catalysts showed the opposite trend. (Me3SiC5H4)TiCl2(O-2,6-iPr2C6H3) displayed the most suitable catalyst performance in terms of its activity and styrene incorporation, affording amorphous copolymers with styrene contents higher than 50 mol% (up to 63.6 mol%) and with random styrene incorporation confirmed by 13C-NMR spectra.